Reconstrução filogenética de Pristocerinae (Hymenoptera, Bethylidae) baseada em dados moleculares - Mugrabi, Daniele Ferreira (2019)
Pristocerinae Mocsáry, composed by 23 genera and 1061 species, are the most numerous subfamily of Bethylidae. The first phylogenetic study carried out in order to understand the relations among the genera of such subfamily was developed by Terayama. He considered most of the genera of Pristocerinae and used morphological characters in order to base his hypotheses. Nevertheless, Terayama did not exploit characters present in the hypopygium and genitalia, which are fundamental structures to delimit the genera of such subfamily. Besides, Terayama used diagnostic characters of the genera as a source of characters for his matrix and polarized them through the use of a hypothetical external group, with plesiomorphic state for all characters, which does not provide robust synapomorphies to test the monophyletism of the genera. Therefore, this study aimed at testing the hypotheses of monophyletism and the previously proposed relations for the genera of Pristocerinae, analyzing the obtained groupings out of the morphostructural characters, especially those of male genitalia and hypopygium. The matrix of characters was built from the sequences of genes COI, 28S, LW Pol2 and EFa2 for 17 of the 23 genera of Pristocerinae. The matrix was analyzed through the use of the estimation methods of maximum likelihood and bayesian inference. As a result, all genera of Pristocerinae were recovered as monophyletic, except Acrenesia. Pseudisobrachium was recovered in a clade separated from all other genera of such subfamily. Calobrachium+Caloapenesia always appear together as sister-group. The clade formed by (Genus A+Foenobethylus+Parascleroderma) was obtained as sister-group of the polytomy formed by (Acrenesia+Cleistepyris) and the clades (Dracunesia+Apenesia (stricto sensu)) and (Eleganesia+Austranesia). A great clade formed by (Genus D+Prostisobrachium+Trichiscus+Genus B+Dissomphalus), sister-group of (Pristocera+Pristepyris+Propristocera) was recovered. The state ‘paramere divided in two arms’ turned out to be homoplastic within Bethylidae. As opposed to that, the state ‘aedeagus divided in two rami’ was recovered as synapomorphic and exclusive to the Pristocerinae. The analyses obtained in this study support the hypotheses of four new genera within the subfamily that were here described and illustrated.